The relationship between levothyroxine dosage and free thyroxine levels in hypothyroid patients: a large retrospective study - Toshihiko Kasahara (European Thyroid Journal)
Objective: This study examined the relationship between levothyroxine dosage and free thyroxine levels in hypothyroid patients. The aim was to ascertain whether elevated free thyroxine in treated patients suggests overmedication or is essential for maintaining appropriate free triiodothyronine levels, guiding improved monitoring practices during therapy. Methods: A retrospective analysis was conducted on 3,020 free thyroxine measurements from 1,409 patients between July 2021 and March 2024. Patients with thyrotropin receptor antibodies or treated with antithyroid drugs such as thiamazole, propylthiouracil, and potassium iodide were excluded. Measurements were performed using the Elecsys FT4 III immunoassay, and statistical comparisons were made between levothyroxine-treated and untreated groups. Results: Levothyroxine-treated patients showed significantly higher median free thyroxine levels (17.9 pmol/L, interquartile range (IQR): 15.6–20.1) than untreated patients (16.2 pmol/L, IQR: 14.5–17.9, P < 0.0001). In addition, the free triiodothyronine/free thyroxine ratio was significantly lower in levothyroxine-treated patients (0.24, IQR: 0.20–0.29) than in untreated patients (0.28, IQR: 0.25–0.32, P < 0.0001). Free thyroxine levels increased with levothyroxine dosage, whereas the free triiodothyronine/free thyroxine ratio decreased. Although thyroid-stimulating hormone levels did not differ significantly between the groups, higher levothyroxine doses were associated with mild suppression. Conclusion: The findings emphasize the importance of higher free thyroxine levels for maintaining adequate free triiodothyronine in levothyroxine-treated patients, underscoring the need to monitor free thyroxine, free triiodothyronine, and their ratio during therapy to optimize treatment outcomes. In addition, clinicians should recognize that higher levothyroxine doses may elevate free thyroxine levels beyond the reference range.